Barriers and facilitators of hepatitis C treatment uptake among people who inject drugs enrolled in opioid treatment programs in Baltimore - Falade-Nwulia, Oluwaseun (J Subst Abuse Treat, 2019)
BACKGROUND: Hepatitis C virus (HCV) infection is a major public health issue among people who inject drugs (PWID) with prevalence of 50–80% in the United States. Effective, simple, oral direct acting agents (DAA) of short duration with minimal side effects have been associated with cure rates > 95%. However, HCV treatment uptake among PWID remains low. We characterized the HCV care continuum, HCV treatment knowledge, as well as barriers and facilitators to HCV treatment uptake among PWID enrolled in two opioid treatment programs (OTPs) in Baltimore, Maryland, USA. METHODS: Between July and November 2016, 124 HCV infected PWID were recruited from two opioid treatment programs in Baltimore through convenience sampling. Participants completed a 50-item questionnaire to assess HCV treatment knowledge, attitudes, and practices. Progress through the HCV care continuum was assessed based on a series of questions assessing evaluation for HCV treatment, recommendation for HCV treatment by a provider, and HCV treatment initiation. HCV status was assessed based on participant self-report. RESULTS: The median age was 52 years (IQR 44–58), 56% were male, the majority were African American (69%), and 19% reported HIV coinfection. Participants had been tested for HCV at their primary care provider’s (PCP’s) office (34%), drug treatment center (20%), emergency room (11%), or prison (9%), and most (60%) had been diagnosed with HCV over 5 years prior. The majority reported that HCV was a major health concern for them (91%), were aware there were new treatments for HCV (89%), and that the new treatments cure most people (69%). More than half (60%) had seen a health professional who could treat HCV, 40% had HCV therapy recommended by their HCV specialist, and 20% had started or completed treatment. In univariable analysis, PWID were significantly more likely to have been treated if they were HIV co-infected (OR 3.4 (95% CI 1.3–9.2)) or had a partner or friend concerned about their HCV (OR 3.4 (95% CI 1.2–9.7)), and were significantly less likely to have been treated if they had used any illicit drugs in the preceding 6 months (OR 0.4 (95% CI 0.2–0.99). In multivariable analysis, having a friend or partner concerned about their HCV remained significantly associated with HCV treatment (OR 5.0 (95% CI 1.4–17.7)). When questioned about what would facilitate HCV treatment, the majority (85%) reported that a friend telling them that HCV treatment had helped them and having HCV treatment provided at their opioid treatment program would make them more likely to engage in HCV treatment. CONCLUSION: Despite a high prevalence of HCV among opioid treatment program patients and the availability of effective treatments, uptake remains low. We identified several key barriers and facilitators that can affect HCV treatment uptake.